Screening African Rice (Oryza glaberrima) for Tolerance to Abiotic Stresses: II. Lowland Drought - Shaibu, A.A.; Uguru, M.I.; Sow, M.; Maji, A.T.; Ndjiondjop, M.N.; Venuprasad, R. (Wiley, 2018)
Drought is a major constraint to rice (Oryza spp.) production in sub-Saharan Africa. Oryza glaberrima Steud., the cultivated rice species that originated from West Africa, is well-adapted to its growing ecologies. This study was initiated to identify promising O. glaberrima accessions tolerant to lowland drought stress from the 2106 accessions held at the AfricaRice Genebank. Screening was done over a 3-yr period in West Africa using standardized protocol and involved evaluating for grain yield under drought and/or irrigated conditions, selecting the high-yielding lines, and repeating the testing with the newly selected lines. Four accessions (TOG 7400, TOG 6520, TOG 6519-A, and TOG 7442-B) with consistently higher grain yield under drought stress and irrigated conditions were selected. These four accessions originated from three countries in West Africa, namely, Ghana, Liberia, and Nigeria. The selected O. glaberrima accessions could be used as donors in breeding for drought tolerance in rice.